Regulation of Th2 responses by Lactococcus lactis subsp. cremoris YRC3780 alleviates DNCB-induced atopic dermatitis in the mouse model. (July 2022) - Wang, Rong; Nakajima-Adachi, Haruyo; Wang, Yimei; Zhou, Yingyu; Gu, Wenting; Hiraide, Erika; Morinaga, Mamiko; Nakagawa, Ryogo; Nakamura, Shotaro; Takano, Tomohiro; Li, Xuyang; Saeki, Mayumi; et al.
Graphical abstract: Highlights: L. cremoris YRC3780 acted on various types of immune cells to inhibit IL-4. L. cremoris YRC3780 regulated Th1/Th2 balance in intestinal DC-T cell coculture. Oral administration of L. cremoris YRC3780 alleviated symptoms in AD mice. L. cremoris YRC3780 inhibited IL-4 in Peyer's patch CD4 + T cells of AD mice. Abstract: Lactococcus lactis subsp . cremoris YRC3780 ( L. cremoris YRC3780) was isolated from kefir, and anti-allergic effects have been confirmed in humans. The mechanisms by which L. cremoris YRC3780 affects the Th1/Th2 balance in mice were investigated in vitro, focusing on the intestinal immune response. Simultaneously, a 2, 4-dinitrochlorobenzene-induced atopic dermatitis mouse model was used to evaluate the symptom improvement effect of oral administration of L. cremoris YRC3780. The results showed that L. cremoris YRC3780 enhanced IFN-γ and IL-12 production and inhibited IL-4 production from CD4 + T cells in the presence of various types of immune cells. Oral administration of L. cremoris YRC3780 attenuated serum total IgE ( p < 0.05) and decreased ear thickness ( p < 0.05) in the atopic dermatitis model. The examination of cytokine expression suggested that L. cremoris YRC3780 improved AD-like symptoms by inhibiting IL-4 gene expression from Peyer's patches CD4 + T cells ( p < 0.01) and IL-33 gene expression ( p < 0.05) in the draining lymph nodes.